Kemandirian Belajar Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Sumatera Utara pada Masa Pandemi Covid-19 - Zuraidah Adlina; Syahlan Syahlan; Asnawati Matondang (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
The Covid-19 pandemic that has been going on since the end of 2019 brings its own paradigm to the learning system that takes place in schools and universities. The purpose of this study was to determine the learning independence students of Universitas Islam Sumatera Utara during the Covid-19 pandemic. This research is a descriptive study that will provide an overview of student learning independence during online lectures in the odd semester of the 2020/2021 academic year. The population in this study were all students of the Faculty of Teacher Training and Education, Universitas Islam Sumatera Utara. Existing samples were selected randomly with a total sample of 60 students. Qualitatively, student learning independence is still in the low category, both in terms of managing study time (26.67%), the ability to complete routine tasks (18.33%), thinking skills (16.67%), the ability to take initiative (28 ,33%), as well as his confidence in learning (26.67%). Therefore, online learning that is implemented needs to be improved to increase student learning independence.